The Relationship Between Social Media Use and the Level Social Anxiety among Female Undergraduate Midwifery Students at Pelamonia Institute of Health Sciences, Makassar - Masahuddin La; Tut Handayani; Eci (Innovative Approaches in Health Science Journal, 2026)
Background: The widespread and excessive use of social media has frequently been associated with the emergence of various psychological disorders, one of which is social anxiety, particularly among female students who access social media with high intensity. Objective: This study aimed to determine whether a relationship exists between social media use and the level of social anxiety among female undergraduate midwifery students at Pelamonia Institute of Health Sciences, Makassar. Methods: This quantitative study employed a descriptive-analytical design with a cross-sectional approach. A total of 86 female students from the Undergraduate Midwifery Study Program of Pelamonia Institute of Health Sciences were selected as respondents through purposive sampling. Data were collected using a social media use questionnaire and the Social Anxiety Scale for Adolescents (SAS-A), and the relationship between variables was tested using the chi-square test (α=0.05). Results: The majority of respondents exhibited high-intensity social media use (96.5%) and were simultaneously classified in the high social anxiety category (96.5%). The chi-square test yielded a p-value of 0.000 (p<0.05), indicating a significant relationship between social media use and the level of social anxiety. Conclusion: A high intensity of social media use was significantly associated with increased social anxiety among female students. Wiser management of social media use, accompanied by psychological counseling programs within the campus environment, is needed to mitigate its adverse effects on female students' mental health.